Chemotherapy for Leukemia Novel Drugs and Treatment - Ueda, Takanori; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book focuses on the latest progress in chemotherapy for leukemia and related diseases, including still-ongoing but promising studies. The effectiveness of treatment for chronic myeloid leukemia and acute promyelocytic leukemia has been dramatically improved in recent years. This improvement has been made possible with the development of molecular targeted agents such as bcr-abl tyrosine kinase inhibitors and all-trans retinoic acid. The antibody for the unique target of chemokine receptor 4 for adult T-cell leukemia/lymphoma, or FLT3 inhibitors (signaling inhibitors) has been applied to other leukemias. Also, chemotherapeutic agents including antimetabolite analogues such as clofarabine, and azacitidine (an epigenetic regulator) have undergone progressive development. Meanwhile, the novel concept of therapy targeting leukemic stem cells has been developed. The contributors discuss prospective results of basic and preclinical studies and clinical possibilities based on the effects for leukemic stem cells. This work facilitates a comprehensive understanding of modern treatment methodology for leukemia. The volume therefore will greatly benefit not only hematologists but also oncologists, all physicians who specialize in blood cancer, and pharmacologists who are involved in the development of therapeutic agents for leukemia.
1 An Overview -- Part I Bcr-Abl Tyrosine Kinase Inhibitors (TKIs) -- 2 Imatinib: Basic Results -- 3 Imatinib: Clinical Pharmacology and Therapeutic Results -- 4 Dasatinib, Nilotinib, Bosutinib, Ponatinib, and Other TKIs -- Part II New Antibodies for Leukemia -- 5 Rituximab and Alemtuzumab for Chronic Lymphocytic Leukemia: Basic Results -- 6 Rituximab and Alemtuzumab for Chronic Lymphocytic Leukemia: Clinical Pharmacology and Therapeutic Results -- 7 Inotuzumab Ozogamicin for Acute Lymphoblastic Leukemia: Clinical Pharmacology and Therapeutic Results -- 8 Blinatumomab for Acute Lymphoblastic Leukemia: Clinical Pharmacology and Therapeutic Results -- 9 Mogamulizumab in Adult T-cell Leukemia/Lymphoma -- Part III Signaling inhibitors -- 10. FLT3 inhibitors -- Part IV Differentiating Agents -- 11 Retinoic Acid, All-Trans Retinoic Acid (ATRA) and Tamibarotene -- 12 The Molecular Basis of Arsenic Trioxide Treatment for Acute Promyelocytic Leukemia (APL) -- 13 Arsenic Trioxide: Clinical Pharmacology and Therapeutic Results -- Part V New Chemotherapeutic Agents Including Antimetabolite -- 14 Nelarabine -- 15 Forodesine -- 16 Clofarabine: Structure, Mechanism of Action, and Clinical Pharmacology -- 17 Clinical Use of Clofarabine for Adults and Children with Leukemia -- 18 Re-Emerging Antimetabolites with Novel Mechanism of Action with Respect to Epigenetic Regulation: Basic Aspects -- 19 Epigenetic Regulator, Re-Emerging Antimetabolites with Novel Mechanism of Action (Azacitidine and Decitabine): Clinical Pharmacology and Therapeutic Results -- Part VI Therapy Targeting Leukemic Stem Cells -- 20 Therapies Targeting Leukemic Stem Cells.
Keywords: Medicine; Hematology; Oncology; Medicine & Public Health; Oncology; Hematology